PERBEDAAN PENGARUH PENDEKATAN PEMBELAJARAN DAN KEMAMPUAN GERAK TERHADAP KETERAMPILAN DASAR PERMAINAN SEPAKBOLA MURID SD FRATER BAKTI LUHUR MAKASSAR - Sakti, Jhon Citro (Lembaga Penelitian dan Pendidikan Mandala, 2022)
Abstract This study is an experimental research type. The population of the study were all sixth grade students of SD Frater Bakti Luhur Makassar with a total sample of 40 students selected by random sampling. Then, the sample division technique used ordinal maching into 20 each group. The data analysis technique used is the 2X2 factorial analysis technique and the Tukey test using the SPSS version 20.00 system at a significant level of 95% or 0,05.Based on the results of data analysis, the study concludes that: (1) there is a difference in the influence of cooperative learning approach and the modified learning approach on basic skills of playing football for students of SD Frater Bakti Luhur Makassar. It can be seen that the Fcount between columns (FA) = 4.340 is greater than Ftable = 4.113. It appears that Fcount > Ftable > or P-value = 0.034 < 0.05 and the modified learning approach (mean = 19.7115 and standard deviation = 2.15129) is better than the cooperative learning approach (mean = 20.2400 and standard deviation = 1.76746), (2) there is an interaction between the learning approach and movement ability on basic skills of playing football for the students of SD Frater Bakti Luhur Makassar. It obtained Fcount interaction (FAB) = 189.838 and Ftable = 4.113. It appears that Fcount > Ftable or P-value = 0,000 < 0.05, (3) there is a difference in basic skills of playing football between the high mobility group using the cooperative learning approach and the modified learning approach, with a P-value of 0.000 less than 0.05, and high mobility using a modified learning approach of 17.7440 better than those using the cooperative learning approach of 21.7680, (4) there is a difference in basic skills of playing football between the low-mobility group using the cooperative learning approach and the modified learning approach, with a p-value of 0.000 greater than 0.05, and low mobility using the cooperative learning approach of 18.7120 better than those using the modified learning approach of 21.6790.